Innovations in improving the professional and practical physical training of students of the military faculty - Khasanov Ahadjon Tursinovich; Siddikov Farrukh Zoirovich; Abduraimov Diyorbek Tavakkalovich (Zien Journals, 2021)
In this article it is presented the results of experiments conducted using a block-module system in the educational process to improve the professional and practical physical training of students of the Faculty of Military Education, and proves the effectiveness of this system in training courses.
Keywords: Physical Training; Physical Qualities; Theoretical Knowledge; Block-Module System